Menimbang Maslahah Sebagai Dasar ‎Penetapan Hukum (Kajian terhadap ‎Pemikiran Muhammad Abu Zahrah)‎ - Abdul Basith Junaidy (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2015)
Abstract: This article tries to describe briefly the views ‎imam Muhammad Abu Zahrah, a leading Islamic jurist from ‎Egypt, relating to the sources of Islamic law and the methods ‎of interpretation contained in his work on the theory of ‎Islamic law, entitled Usul al-Fiqh, with a primary focus on ‎one of the interpretations of the sources of law, namely ‎maslahah through by theory of maqasid al-Sharia. At the end ‎of the article concluded that in Islamic law, maslahah was the ‎main purpose and first in muamalah problems. Maslahah can ‎be seen in the short-term purpose and long-term purpose, and ‎has been agreed as a proposition of law jurists law. ‎Nevertheless, there are differences of opinion with regard to ‎the levels of use of pure reason in an attempt to find the ‎maslaah unaided nass at all, the opinion of one effusive in ‎adhering to pure reason, and another opinion effusive in ‎stopping the nass. But Imam Malik ibn Anas, is in the middle ‎of these two opinions, by not making